ONLINE ASSESSMENT PEMBELAJARAN NEO GUIDED INQUIRY BERBASIS LITERASI DAN NUMERASI PADA MAHASISWA - Salis Irvan Fuadi; Pamungkas Stiya Mulyani (Muróbbî: Jurnal Ilmu Pendidikan, 2022)
The purpose of this study was to find out how the product development process and the online assessment model for Neo Guided Inquiry Learning Based on Literacy and Numeration in Students The specific purpose of this study was to see the response of the development of the Online Assessment of Neo Guided Inquiry Learning Based on Literacy and Numeracy in Students. This research was carried out with a Research and Development design that adopted the Borg & Gall model. The research uses quantitative and qualitative methods. The quantitative method is carried out by measuring using a Likert Scale questionnaire with 4 (Four) Standards and the respondents are students and lecturers, then converted into numerical data to be tabulated. Qualitative methods using observations and questionnaires that aim to be used to find out the needs and inputs of users of products and models and ensure that the learning application process is in accordance with the learning syntax model. Observation directly to get information about obstacles or problems at the time of testing. Sampling planning and instruments that have been validated by three expert validators and adapted to the needs of the data.Keywords: Online Assessment, Neo Guided Inquiry, Literacy, Numeration